Use of Monolingual English Guidelines to Assess Stuttering in Bilingual Speakers: A Systematic Review - Byrd, Courtney; Werle, Danielle; Coalson, Geoffrey A.; Eggers, Kurt (Journal of Monolingual and Bilingual Speech, 2020)
Speech-language pathologists can identify stuttering in multiple languages, even if they do not speak the language. However, due to differences in language development, multilingual speakers have been documented with higher levels of typical disfluencies in their speech than monolingual speakers. These higher levels of disfluency put multilingual speakers at greater risk of misdiagnosis as individuals who stutter, due to poor understanding of the nature of the manifestation of stuttering in two or more languages and reliance on monolingual-English diagnostic criteria. The purpose of the present systematic review is to explore how stuttering is identified in multilingual speakers who are described as participants who stutter, and whether monolingual English-speaking guidelines were the most commonly used reference for determining the presence of stuttering.